PERAN GREEN TRANSFORMATIONAL LEADERSHIP DALAM MEMBENTUK ORGANIZATIONAL CITIZENSHIP BEHAVIOR: PERSPEKTIF GREEN ORGANIZATIONAL CULTURE - Ardiani, Gusti Tia; Supriadi, Apip (Jurnal Ekonomi Manajemen, 2024)
ABSTRACTThe purpose of this study was to determine and analyze the role of Green Transformational Leadership in shaping Organizational Citizenship Behavior: Perspective of Green Organizational Culture in frontline employees of PT NICESO Sukses Indonesia. The research method used is the survey method, while the sample withdrawal uses the census method. through questionnaires from 39 respondents The analysis tool uses multiple regression tests. The results showed that there was an influence of green organizational culture and green transformational leadership on organizational citizenship behavior. Keywords: green organizational culture; green transformational leadership; organizational citizenship behavior.ABSTRAKTujuan penelitian ini adalah untuk mengetahui dan menganalisis Peran Green Transformational Leadership dalam Membentuk Organizational Citizenship Behavior: Perspektif Green Organizational Culture pada karyawan bagian frontliner PT.NICESO Sukses Indonesia. Metode penelitian yang digunakan adalah metode survey, sedangkan penarikan sampel menggunakan metode sensus. melalui kuesioner dari 39 responden Alat analisis menggunakan uji regresi berganda. Hasil penelitian menunjukkan bahwa terdapat pengaruh green organizational culture dan green transformational leadership Terhadap organizational citizenship behavior Kata Kunci: green organizational culture; green transformational leadership; organizational citizenship behavior.